Direct printing of soluble acene crystal stripes by a programmed dip-coating process for organic field-effect transistor applications. Issue 4 (8th January 2018) - Nam, Sooji; Jeong, Yong Jin; Jung, Jaemin; Kim, Se Hyun; Ahn, Jinho; Shin, Kwonwoo; Jang, Jaeyoung
Abstract : High-crystalline TIPS-PEN crystal stripes are directly printed with controllable inter-stripe spacing via programmed dip-coating for application in organic field-effect transistors. Abstract : Functionalized soluble acenes have great potential for use as semiconducting layers in organic electronic devices because of their easy processability and good intrinsic field-effect mobilities. Commercialization of organic devices based on these semiconductors requires the development of facile patterning methods and deposition techniques that induce high crystallinity. In this study, we report the direct printing of highly crystalline soluble acene crystal stripes via a novel programmed dip-coating technique. The acene crystals are successfully patterned into an array of stripes with controllable inter-stripe spacing, using a low boiling point solvent and adjusting the lifting rate of the substrate in the programmed dip-coating process. The patterned thin films showed a well-ordered molecular structure with high crystallinity, which is advantageous for efficient charge transport. Finally, the acene crystals patterned by programmed dip-coating were employed as active channels in organic field-effect transistors. The resulting devices exhibited superior electrical properties compared to those of the devices based on spin-coated films. Our strategy to prepare acene crystal patterns via programmed dip-coating will enrich the current solution-based thin film technologies by providing another viable option for direct patterning, while optimizing the morphology and crystallinity of the printed pattern.